Tenorio syndrome: Description of 14 novel cases and review of the clinical and molecular features. Issue 4 (16th July 2021) - Tenorio‐Castaño, Jair Antonio; Arias, Pedro; Fernández‐Jaén, Alberto; Lay‐Son, Guillermo; Bueno‐Lozano, Gloria; Bayat, Allan; Faivre, Laurence; Gallego, Natalia; Ramos, Sergio; Butler, Kameryn M.; Morel, Chantal; Hadjiyannakis, Stasia; et al.
Abstract: Tenorio syndrome (TNORS) (OMIM #616260) is a relatively recent disorder with very few cases described so far. Clinical features included macrocephaly, intellectual disability, hypotonia, enlarged ventricles and autoimmune diseases. Molecular underlying mechanism demonstrated missense variants and a large deletion encompassing RNF125, a gene that encodes for an U3 ubiquitin ligase protein. Since the initial description of the disorder in six patients from four families, several new patients were diagnosed, adding more evidence to the clinical spectrum. In this article, we described 14 additional cases with deep phenotyping and make an overall review of all the cases with pathogenic variants in RNF125 . Not all patients presented with overgrowth, but instead, most patients showed a common pattern of neurodevelopmental disease, macrocephaly and/or large forehead. Segregation analysis showed that, though the variant was inherited in some patients from an apparently asymptomatic parent, deep phenotyping suggested a mild form of the disease in some of them. The mechanism underlying the development of this disease is not well understood yet and the report of further cases will help to a better understanding and clinical characterization of the syndrome. Abstract :